Surgical treatment of patients with nodular toxic goiter - S. M. Zavhorodnii; M. S. Gatia; М. А Kubrak; M. B. Danyliuk (Zaporožskij Medicinskij Žurnal)
Nodular toxic goiter (NTG) accounts for 7.3 % to 10.0 % of the goiter population. There are difficulties in the preoperative differential diagnosis between NTG and other thyroid diseases. There is also controversy about the benefits of resection surgery over thyroidectomy in patients with NTG.